1985
DOI: 10.1042/bj2290679
|View full text |Cite
|
Sign up to set email alerts
|

Solubilization and characterization of pellet-associated human brain α-L-fucosidase activity

Abstract: The pellet-associated portion of human brain alpha-L-fucosidase (which represents approx. 20% of the homogenate activity) was solubilized with 0.5% (w/v) Triton X-100, characterized with regard to several properties and compared with the corresponding properties of the soluble supernatant-fluid enzyme in an attempt to find a second alpha-L-fucosidase in human brain. The solubilized and soluble alpha-L-fucosidase activities exhibited complete stability after storage at 2-4 degrees C for up to 29 days, comparabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 15 publications
4
6
0
Order By: Relevance
“…Our findings are very unusual since almost all previous studies have found that mammalian fucosidases are associated with lysosomes and have relatively acidic pH optima between 4 and 6 [1]. The pellet-associated human brain fucosidase has a pH optimum of 5.5-6.0 [21] and purified rat liver [23] and cerebral cortex [24] α--fucosidases have pH optima of 5.7-5.9 and 4.3, respectively. In addition and more specifically, previous studies on rat epididymal fucosidase [25][26][27] have found pH optima (5.5-6.5) lower than the pH 7.0 value which we have observed.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Our findings are very unusual since almost all previous studies have found that mammalian fucosidases are associated with lysosomes and have relatively acidic pH optima between 4 and 6 [1]. The pellet-associated human brain fucosidase has a pH optimum of 5.5-6.0 [21] and purified rat liver [23] and cerebral cortex [24] α--fucosidases have pH optima of 5.7-5.9 and 4.3, respectively. In addition and more specifically, previous studies on rat epididymal fucosidase [25][26][27] have found pH optima (5.5-6.5) lower than the pH 7.0 value which we have observed.…”
Section: Discussionmentioning
confidence: 49%
“…This is a very novel finding for this enzyme since the great majority (90-100 %) of α--fucosidase activity in almost all mammalian tissues investigated is in the soluble fraction [1]. Human brain is an exception in that it contains a pellet-associated α--fucosidase but it only represents approximately 30 % of the recovered activity from brain homogenates [21]. Approximately 90 % of the epididymal sperm pellet-associated α--fucosidase activity could be extracted with phosphate buffer containing 0.5 M NaCl compared with only 10 % of the activity with phosphate buffer containing 0.5 % Triton X-100.…”
Section: Discussionmentioning
confidence: 73%
“…Resuspension was followed by recentrifugation at 25 500 g for 45 min. Solubilization of human brain pellet-associated a-L-fucosidase was carried out as previously described (Hopfer & Alhadeff, 1985). The twice-washed pellet was resuspended in phosphate buffer containing 0.5% (w/v) Triton X-100, homogenized by use of the Potter-Elvehjem tissue grinder as described above and centrifuged at 25000 g for 45 min.…”
Section: Generalmentioning
confidence: 99%
“…Isoelectric focusing of purified pellet-associated brain a-L-fucosidase was accomplished as previously described for crude preparations of pellet-associated human brain a-L-fucosidase (Hopfer & Alhadeff, 1985). ac-L-Fucosidase activity (6.4 units) was loaded on an LKB 8100 (110 ml) Ampholine column with Ampholytes (pH 5-8;…”
Section: Isoelectric Focusingmentioning
confidence: 99%
See 1 more Smart Citation